Clinical characteristics and surgical treatment comparison of multisegmental spinal tuberculosis: a retrospective analysis - Zongqiang Yang; Zongqiang Yang; Zhangui Gu; Zhangui Gu; Qiang Liu; Qiang Liu; Long Ma; Le Fei; Le Fei; Ningkui Niu; Ningkui Niu; Jiandang Shi (Frontiers in Medicine)
BackgroundTo analyze the therapeutic efficacy of intervertebral surgery in the treatment of multisegmental spinal tuberculosis (MSTB) by evaluating its clinical outcomes and perioperative indicators, thereby providing evidence-based insights to optimize surgical strategies and improve clinical decision-making.MethodsThis retrospective cohort study analyzed 134 MSTB patients treated at our hospital between January 2000 and June 2022. Based on the surgical approach, patients were divided into two groups: Group A (n = 75), who underwent intervertebral surgery, and Group B (n = 59), who received non-intervertebral surgery. All patients underwent radical debridement, bone graft fusion, spinal canal decompression, and internal fixation to restore spinal alignment. To compare the clinical outcomes of these two surgical approaches, we assessed perioperative parameters, radiographic outcomes, laboratory inflammatory markers, neurological recovery, and complication rates. Statistical analyses included t-tests or Mann–Whitney U tests for continuous variables and chi-square or Fisher’s exact tests for categorical variables.ResultsThe mean follow-up duration was 63.24 ± 9.16 months for Group A and 64.05 ± 9.74 months for Group B. Group A demonstrated significantly shorter operative time and reduced intraoperative blood loss compared to Group B (p < 0.05). No significant differences were observed between the groups regarding preoperative, 6-month postoperative, and final follow-up values of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) levels, Cobb angle, or visual analog scale (VAS) scores (p > 0.05). Bone fusion rates were comparable between the two groups at 6 months, 1 year postoperatively, and at final follow-up, with complete fusion achieved in all patients (p > 0.05). The incidence of postoperative complications and neurological recovery rates did not differ significantly between the two groups (p > 0.05).ConclusionBoth intervertebral and non-intervertebral surgical strategies for MSTB can effectively restore spinal alignment and achieve satisfactory neurological recovery, provided that strict surgical indications are adhered to. Intervertebral surgery, with its shorter operative time and lower intraoperative blood loss, may offer additional perioperative advantages and serve as a viable option for MSTB management.